Jogos no ciclo de alfabetização: contribuições para a leitura e a escrita - Silva, Solange Pereira da (Brasil, 2023)
This study aims to socialize the relevance of games and games for the development of literacy and literacy, since, although there are many studies on the use of play as a mediation for teaching and learning, it is still a didactic - pedagogical resource little used in the classroom. This is bibliographic research in dialogue with theorists who address the subject, in primary works, as well as in scientific articles. In the analysis of literacy games suggested by some authors, we found the possibilities of contact with reading and writing in a playful way, followed by other activities of linguistic analysis, such as word formation, identification of syllables and rhymes, construction of phrases associated with reading and writing and emphasis on phonemic awareness - sound – letter – sound – spelling relationship, contemplating the alphabetic writing system as the initial linguistic basis of literacy. Faced with these findings, we affirm that the ludic and ludic activities can enhance the work with reading and writing in literacy.